INFLUENCE MARKETING IN THE DIGITAL ECONOMY - Tomchuk-Ponomarenko, N.; Kobets, D.; Lytovchenko, V. (Socio-economic relations in the digital society, 2021)
The essence of influence marketing is investigated in the article. The mechanisms of influence marketing are defined and a brief description of each of them is given, namely: the star effect, to reach the right audience, the right tone, confidence in communication, long-term operation. According to the results of 2020, the most popular Facebook pages among retailers in Ukraine were Rozetka, Watsons Ukraine and the EVA Store Line. And, as before, in the final triumvirate, two chains of drogerie stores at the same time. Antoshka and Allo swapped places on the fourth and fifth steps. The underdevelopment of the digital economy can have negative consequences for the interests of consumers and the functioning of economic entities. This problem significantly hinders the maintenance of the necessary balance of interests of business entities, society and thestate in the information sphere. The stages of marketing influence in the digital economy are constructed. Studies show that it is easier for a blogger to communicate and attract the attention of a narrow audience, which makes product/brand advertising more effective in collaboration with micro-influencers. Thus, we summarize the key benefits of using a thought leader as a communication tool in the marketing activities of companies, namely: researching the characteristics of target consumers when choosing a blogger, jointly developing the concept of advertising a product or service, implementing influence marketing through social networks, evaluating the advertising campaign, creating a department of influence marketing. The stages of marketing influence in the digital economy, which will help the company to be more competitive, are substantiated, which include: research of the characteristics of target consumers when choosing a blogger; joint development of the conceptof advertising a product or service; introduction of influence marketing through social networks; evaluation of the advertising campaign; creation of an impact marketing department. It has been proven that influence marketing is becoming an increasingly important format in the field of digital marketing, as it allows you to effectively build communication with the target group and attract new ones.
Keywords: marketing; activity; bloggers; retail; enterprise; competitiveness; stages